0488 Trajectories of Insomnia Symptoms since Childhood Associated with Treatment of Internalizing Disorders in Adulthood. (25th May 2022) - Singh, Rupsha; Lenker, Kristina; Calhoun, Susan; Ricci, Anna; Liao, Jason; He, Fan; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward; Fernandez-Mendoza, Julio
Abstract: Introduction: Internalizing disorders (ID) are the most common form of psychopathology, with a large proportion of individuals seeking treatment in young adulthood. Childhood insomnia symptoms, i.e., difficulties initiating or maintaining sleep (DIMS), have been shown to be associated with ID, however, little is known about the developmental trajectories of insomnia symptoms and their associated risk of receiving pharmacotherapy for ID. The present study examined the longitudinal association between trajectories of childhood insomnia symptoms and risk of receiving treatment for ID in young adulthood. Methods: We analyzed data from the Penn State Child Cohort, a population-based sample of 505 children (Mdn=9y), who were followed-up 8 years later as adolescents (Mdn=16y) and 15 years later as young adults (Mdn=24y). Insomnia symptoms were defined as parent-reported (childhood) or self-reported (adolescence and young adulthood) moderate-to-severe DIMS. The trajectories of insomnia symptoms across the three time-points were identified as never, remitted, waxing-and-waning, incident and persistent. The presence of ID was defined as a self-report of a diagnosis of mood and/or anxiety disorders, whether they had received treatment or not and whether treatment consisted of prescription psychotropic medication (i.e., antidepressants, anxiolytics). Logistic regression models were adjusted for sex, race/ethnicity, age, and any childhood or adolescent history of a psychiatric diagnosis or psychotropic medication use. Results: Persistent (OR=3.0) and incident (OR=3.3) trajectories, but not waxing-and-waning (OR=1.1) or remitted (OR=0.8) trajectories, were associated with increased odds of ID that did not receive treatment in adulthood. Additionally, the odds of receiving treatment for ID with prescription psychotropic medication in adulthood were increased in those with persistent (OR=3.4), incident (OR=3.5) and waxing-and-waning (OR=2.1) trajectories, but not in those with a remitted trajectory (OR=0.7). Conclusion: Childhood-onset persistent insomnia symptoms as well as adult-onset incident insomnia symptoms are strong risk factors for receiving treatment for mood/anxiety disorders in adulthood, while childhood insomnia symptoms that fully remit over time are not. Treatment of insomnia in youth should be an essential target as to decrease the risk of developing severe forms of mood/anxiety disorders requiring psychotropic treatment in adulthood. Support (If Any): National Institutes of Health (R01HL136587, R01MH118308, UL1TR000127)